2018
DOI: 10.21037/jtd.2018.05.141
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive miRNA markers for the detection and management of NSTEMI acute myocardial infarction patients

Abstract: miRNA is a potentially sensitive biomarker for NSTEMI AMI patients for disease detection and treatment monitoring. The sensitivities were comparable to cTnT for diagnostic accuracy and patients with sustained or higher levels were correlated to secondary complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 34 publications
1
39
1
1
Order By: Relevance
“…Further subgroup analysis was performed in order to determine whether the distinction between STEMI and NSTEMI might account for some of the conflicting reports regarding increased Mir-133a concentrations following AMI. Relying on six papers that reported the percentage of STEMI patients in the study [17,18,20,21,24,37], and a linear regression model plotting Mir-133a fold as a function of this percentage, we found a moderate correlation (r = 0.49), with a trend of increasing Mir-133a concentration with higher percentages of STEMI patients ( Figure 3a). Furthermore, we compared subgroups from studies that reported data separately for STEMI or NSTEMI patients [17,18,20,21,24] and found a significantly higher value (p < 0.001) of the Mir-133a fold increase in STEMI patients vs. NSTEMI patients (11.6 ± 0.72 fold vs. 4.5 ± 0.14 fold, respectively; Figure 3b).…”
Section: Meta-analysis Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…Further subgroup analysis was performed in order to determine whether the distinction between STEMI and NSTEMI might account for some of the conflicting reports regarding increased Mir-133a concentrations following AMI. Relying on six papers that reported the percentage of STEMI patients in the study [17,18,20,21,24,37], and a linear regression model plotting Mir-133a fold as a function of this percentage, we found a moderate correlation (r = 0.49), with a trend of increasing Mir-133a concentration with higher percentages of STEMI patients ( Figure 3a). Furthermore, we compared subgroups from studies that reported data separately for STEMI or NSTEMI patients [17,18,20,21,24] and found a significantly higher value (p < 0.001) of the Mir-133a fold increase in STEMI patients vs. NSTEMI patients (11.6 ± 0.72 fold vs. 4.5 ± 0.14 fold, respectively; Figure 3b).…”
Section: Meta-analysis Resultsmentioning
confidence: 86%
“…The remaining 23 eligible studies [10][11][12][16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34][35][36] were thoroughly analyzed and subjected to the above inclusion criteria ultimately yielding 9 studies (Table 1) involving 2280 participants, with 943 AMI patients and 1337 controls that were included in the quantitative meta-analysis. AMI-acute myocardial infarction; STEMI-ST elevation myocardial infarction; NSTEMI-non-ST elevation myocardial infarction; AUC-area under the curve.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations